DIANA‐TarBase and DIANA Suite Tools: Studying Experimentally Supported microRNA Targets. Issue 1 (7th September 2016) - Paraskevopoulou, Maria D.; Vlachos, Ioannis S.; Hatzigeorgiou, Artemis G.
Abstract: microRNAs (miRNAs) are short non‐coding RNAs (∼22 nts) present in animals, plants, and viruses. They are considered central post‐transcriptional regulators of gene expression and are key components in a great number of physiological and pathological conditions. The accurate characterization of their targets is considered essential to a series of applications and basic or applied research settings. DIANA‐TarBase (http://www.microrna.gr/tarbase ) was initially launched in 2006. It is a reference repository indexing experimentally derived miRNA‐gene interactions in different cell types, tissues, and conditions across numerous species. This unit focuses on the study of experimentally supported miRNA‐gene interactions, as well as their functional interpretation through the use of available tools in the DIANA suite (http://www.microrna.gr ). The proposed use‐case scenarios are presented in protocols, describing how to utilize the DIANA‐TarBase database and DIANA‐microT‐CDS server and perform miRNA‐targeted pathway analysis with DIANA‐miRPath‐v3. All analyses are directly invoked or initiated from DIANA‐TarBase. © 2016 by John Wiley & Sons, Inc.